DARI SIKAP PEDULI SOSIAL REMAJA MENUJU PEMBIASAAN INFAK DAN SEDEKAH: STUDI FILANTROPI SOSIAL PADA FORUM KOMUNIKASI REMAJA MASJID LEBAK, RANGKASBITUNG - Euis Ismayati Yuniar (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2021)
The objectives to be achieved in this study are to: analyze the influence between the habit of infaq and alms together towards the development of adolescent social care attitudes at the Lebak Rangkasbitung Mosque Youth Communication Forum. This quantitative research uses the Pre Experimental Design method, with the One-Shot Case Study approach model, which is an approach model that uses one time data collection at a "time". The data source comes from a questionnaire, at the implementation stage respondents were given special treatment or teaching for some time, namely the use of infaq and alms habituation. Then at the end of the program, respondents were given a questionnaire of 20 statements. The process of analyzing this research uses product moment correlation test significance. The results of the study are: (1) variable X1 (customization of infaq) obtained an average score of 77, including both categories. (2) variable X2 (alms habituation), obtained an average score of 80, including both categories. (3) variable Y (adolescent social care attitude) from the results of questionnaire distribution obtained an average score of 84, including the excellent category. Based on the results of the 't test' hypothesis significance influence between habituation (X1) and alms habit (X2) together on adolescent social care attitudes (Y), namely the value of t count 10.35467> t table 6.296 with a significance level of 0.05 and degrees of freedom (dk) = 40-2 = 38 then H0 is rejected. Thus it can be concluded that the higher the value of donation and habituation habituation, the higher the development of adolescent social care attitudes.